WOMEN AND WORK: DEMAND FOR LOW-PAID WORK AND MOVEMENT TO CITIES IN KERALA - Alexander, Elizabeth (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Despite the achievements of the Indian state of Kerala in development indicators with a negligible gender gap, when it comes to employment, the performance of women’s paid participation falls below expectations. The low work participation rate of women in Kerala over the decades has been showing signs of improvement in the recent PLFS surveys. Apart from the reported increase in work through Kudumbaree and MGNREGA, the paper argues that the recent economic changes have created an increase in demand for low-paid work of women, contributing to this change. The paper tries to understand the nature of this demand created especially in the cities, by focusing on two low-end categories of work -salesgirls and domestic workers. The paper also tries to trace an emerging pattern of intrastate movement of women for work in the cities in these newly created job opportunities. The paper is based on primary survey, supplemented by secondary data and literature.